What is honor? a question of moral imperatives - Welsh, Alexander 1933-2018 (Yale University Press, 2008)
On moralities of obedience and respect -- Help from anthropology and psychology -- Respect in the ethics of Aristotle -- Cicero's mediation of the same -- Shakespeare's recourse to Roman honor -- His Antony, Cleopatra, and Coriolanus -- Honor by that name in Mandeville and Montesquieu -- Leveling down in Enlightenment fiction -- Coming of age in neoclassical drama -- And how Rousseau's Emile comes of age -- Kant's engagement with honor -- Parallels to Kant's moral philosophy -- Respect and Adam Smith's impartial spectator -- Adam Smith and recent social science -- Coming to terms with honor in philosophy